Pembaruan Aplikasi Paperless Office Universitas Syiah Kuala - Taufik Fuadi Abidin; Fitra Riyanda; Rahmad Dawood (Universitas Syiah Kuala, 2016)
Paperless Office (PLO) is a web-based application that was created to facilitate digital office communication such as sending memos, letters, and posting news. It was initially created by Bambang Prastowo from Universitas Gajah Mada. The goals of using PLO are to reduce paper usage, speed up internal communication, and to simplify the management of correspondence in digital form. Syiah Kuala University (Unsyiah) has implemented PLO since early 2013. This paper aims to analyze the level of activity and users satisfaction of the renew PLO. The renew is done by making the web application more responsive and adding new features that do not exist in the earlier version. The results show that users satisfaction level increases, observed from system quality, information, and services. Variables that affect the level of activity, based on Pearson and Spearman correlations, are X1, X13,X20,X33, X36,X38, andX43, while the variables that affect the level of users satisfaction are X42 and X44.